Liabilities and court-supervised reorganization: an analysis of behavior in public companies (Revista Brasileira de Contabilidade e Gestão, 2022)
The objective of the study has been to analyze the behavior of liabilities after compliance with the court-supervised reorganization process in order to verify if the compliance is signaling that companies meet the objective of the process, that is, if they are fulfilling the passive liabilities assumed and are continuing their activities with optimization of their financial capacity, in this way indicating to the market the search for economic and financial reestablishment. The research is quantitative and to achieve its objective balance sheet data and income statements were collected from 38 companies of the Brazilian Stock Exchange from 2011 to 2018, where 19 companies are under court-supervised reorganization process and 19 are not. Thus, the behavior of the liability balances of the companies has been verified for the study period linked to indebtedness and liquidity financial ratios to verify if the companies that are undergoing reorganization have reduced their liabilities with consequent optimization of the ratios. To reach this objective, a panel data regression model has been estimated. As a result of the survey, this study has found that approximately 65% of the companies that comply with the court-supervised reorganization process have a high degree of bank debt at the time of recovery, and this group is the main component of their liabilities. In addition, it has also been found that compliance with the reorganization plan indicates that companies use the reorganization process as an alternative to avoid bankruptcy and that they have difficulty recovering their financial and economic ability.
Keywords: liabilities; court-supervised reorganization; signaling theory; financial accounting; financial; business behavior; public companies